2017
DOI: 10.1186/s40621-017-0115-x
|View full text |Cite
|
Sign up to set email alerts
|

Injury, intense dust exposure, and chronic disease among survivors of the World Trade Center terrorist attacks of September 11, 2001

Abstract: BackgroundThe World Trade Center attack of September 11, 2001 in New York City (9/11) exposed thousands of people to intense concentrations of hazardous materials that have resulted in reports of increased levels of asthma, heart disease, diabetes, and other chronic diseases along with psychological illnesses such as post-traumatic stress disorder (PTSD). Few studies have discriminated between health consequences of immediate (short-term or acute) intense exposures versus chronic residential or workplace expos… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
32
1

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 24 publications
(35 citation statements)
references
References 33 publications
2
32
1
Order By: Relevance
“…Also, it corresponds with findings from other studies on injured survivors after the July 22nd attacks demonstrating high levels of various somatic health problems both among hospitalized and non-hospitalized injured survivors (Grimholt et al, 2018;Manum et al, 2019;Wisloff-Aase et al, 2019). In the long-term aftermath of the attacks, studies have reported positive significant associations between trauma-sustained injury and heart and respiratory disease and reported reduced physical health functioning (Alper et al, 2017;Brackbill et al, 2019;Brackbill et al, 2014). Both being caught in the dust cloud and distress from being injured contributed to respiratory disease for this group (Brackbill et al, 2014).…”
Section: Physical Injury and Somatic Complaintssupporting
confidence: 88%
See 3 more Smart Citations
“…Also, it corresponds with findings from other studies on injured survivors after the July 22nd attacks demonstrating high levels of various somatic health problems both among hospitalized and non-hospitalized injured survivors (Grimholt et al, 2018;Manum et al, 2019;Wisloff-Aase et al, 2019). In the long-term aftermath of the attacks, studies have reported positive significant associations between trauma-sustained injury and heart and respiratory disease and reported reduced physical health functioning (Alper et al, 2017;Brackbill et al, 2019;Brackbill et al, 2014). Both being caught in the dust cloud and distress from being injured contributed to respiratory disease for this group (Brackbill et al, 2014).…”
Section: Physical Injury and Somatic Complaintssupporting
confidence: 88%
“…Further, the predictive value of clinical measures of injury severity, such as ISS, have been investigated in a few studies, but the findings differ and are inconclusive (Greenspan & Kellermann, 2002;van Delft-Schreurs et al, 2017;Zatzick et al, 2003). A dose-response relationship has been found between number of injury types and later medical diagnoses (Alper, Yu, Stellman, & Brackbill, 2017;Brackbill et al, 2014). Further, initial pain levels and pain control, injuries to the brain, spinal cord, lower extremities, and longer hospitalization have been found to predict poorer selfreported physical health (Holmes et al, 2010;Ramchand et al, 2008;Soberg et al, 2012;Toft, Moller, & Laursen, 2010;van Delft-Schreurs et al, 2017).…”
Section: Models and Predictors For The Development Of Somatic Complaintsmentioning
confidence: 99%
See 2 more Smart Citations
“…Increased risk of cardiovascular disease (CVD) has been linked to airborne particulate exposures [ 136 ] and severe psychological stress [ 136 , 137 , 138 , 139 ]; therefore, WTC exposures and experiences may potentially increase CVD risks. The relationship between WTC exposures and CVD has been examined in several studies [ 54 , 76 , 140 , 141 , 142 , 143 , 144 , 145 , 146 , 147 ]. Registry enrollees were studied most often [ 54 , 141 , 143 , 144 , 145 , 146 , 147 ].…”
Section: Research Portfoliomentioning
confidence: 99%